2003
DOI: 10.1381/096089203322190835
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms are More Intense in Morbidly Obese Patients and are Improved with Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Morbidly obese patients experience more intense GI symptoms than control subjects, and many of these symptoms return to control levels 6 months after LRYGBP. Dysphagia is equivalent to control subjects preoperatively but increases significantly after LRYGBP. This data suggests another quality-of-life improvement (relief of GI symptoms) for morbidly obese patients. Further follow-up is needed to document the long-term reduction of GI symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 12 publications
2
76
0
4
Order By: Relevance
“…My results are similar to those of most studies which show a positive association between IBS and general obesity [15,16,17]; and between IBS and central obesity [14]. Some studies show that central obesity using WC is more associated with IBS than general obesity [18,19].…”
Section: Association Between Central Obesity and Ibssupporting
confidence: 88%
“…My results are similar to those of most studies which show a positive association between IBS and general obesity [15,16,17]; and between IBS and central obesity [14]. Some studies show that central obesity using WC is more associated with IBS than general obesity [18,19].…”
Section: Association Between Central Obesity and Ibssupporting
confidence: 88%
“…Some studies that included patients with MO and RYGBP have reported complete improvement of symptoms in 80% of the cases and discontinuation of anti-secretory therapy in 97% of the patients [24,25,[34][35][36]. In patients with lesser degrees of obesity (BMI 35-39.9 kg/m 2 ), symptom improvement has been observed after a RYGBP surgery [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of patients experience improvement in functional gastrointestinal disorders, some may develop exacerbations of symptoms 51 . The role of the emergency surgeon is to have a basic understanding of the likely cause of these symptoms.…”
Section: Functional and Nutritional Complicationsmentioning
confidence: 99%